2017
DOI: 10.1007/s12402-017-0238-5
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analytic review of the association between cortisol reactivity in response to a stressor and attention-deficit hyperactivity disorder

Abstract: A substantial literature suggests that abnormal cortisol reactivity may be a vulnerability for deleterious mental health outcomes, including ADHD. ADHD has been linked with difficulty in emotion regulation and increased risk of experiencing stressors, both of which may be related to psychobiological abnormalities (e.g., abnormal cortisol reactivity). Research has been mixed regarding the association between cortisol reactivity and ADHD. Therefore, the present meta-analytic review (k = 12) sought to quantify th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 59 publications
0
16
0
2
Order By: Relevance
“…A blunted cortisol response, such as we identified in the ADHDt children, had been identified by previously in children with ADHD as a whole, and within a population of children with ADHD and behavioral co-morbidities (King et al, 1998; Maldonado et al, 2009; Van West et al, 2009). However, these findings are quite inconsistent across studies (Kamradt et al, 2018). Kamradt et al (2018) indicate that a link between the HPA axis and ADHD had been found for children with severe externalizing behaviors, and that these behaviors might be the driver of this relationship.…”
Section: Adhd Cortisol Electrodermal Response and Anxiety: Findingmentioning
confidence: 97%
“…A blunted cortisol response, such as we identified in the ADHDt children, had been identified by previously in children with ADHD as a whole, and within a population of children with ADHD and behavioral co-morbidities (King et al, 1998; Maldonado et al, 2009; Van West et al, 2009). However, these findings are quite inconsistent across studies (Kamradt et al, 2018). Kamradt et al (2018) indicate that a link between the HPA axis and ADHD had been found for children with severe externalizing behaviors, and that these behaviors might be the driver of this relationship.…”
Section: Adhd Cortisol Electrodermal Response and Anxiety: Findingmentioning
confidence: 97%
“…The hypothalamus-pituitary-adrenal axis (HPA axis) is an important responder to stressful environments. Several studies have shown that stress reactions are different in ADHD patients compared to healthy controls [148][149][150][151] . ADHD patients show reduced diurnal cortisol levels compared to healthy controls 152,153 .…”
Section: Stress and Adhdmentioning
confidence: 99%
“…A genetic family-based study found an association between functional polymorphisms of the gene encoding the glucocorticoid receptor and childhood ADHD-related behaviors, which, given the pivotal role of glucocorticoid receptor on the HPA axis, suggests a possible involvement of the HPA axis in ADHD [ 51 ]. Many studies have focused on differences in cortisol level, particularly in stress responsivity [ 52 , 53 ], although there has been significant heterogeneity in approach and findings have been inconclusive, particularly with respect to differences in ADHD subtype, presence of co-occurring mental health conditions, and sex. Studies on the relationship between androgen levels and attention and conduct problems in children and adolescents have been similarly divergent [ 14 , 54 , 55 ], likely because of the diversity of specific hormones being investigated, consideration of prenatal versus postnatal exposures, and the complicating role of sex.…”
Section: Discussionmentioning
confidence: 99%